One-step green hydrothermal synthesis of biocompatible graphene/titanium dioxide nanocomposites: towards the development of highly sensitive and selective electrochemical immunosensor for dengue diagnosis - Siew, Qi Yan (2020)
Biosensor platforms are powerful analytical devices capable of revolutionising medical diagnostics by providing highly accessible and effective diagnosis at the point-of-care stage. In this work, a high-performance electrochemical-based biosensing platform was developed using graphene/titanium dioxide (G/TiO2) nanocomposite. The graphene employed in the G/TiO2 electrode material was synthesised via a sonochemical liquid phase exfoliation method, eradicating the use of harsh chemicals and high temperature conditions. The simple and low temperature hydrothermal synthesis of the G/TiO2 nanocomposite also ensured the affordability and scalability of the process. Modifying electrodes with the as-synthesised nanocomposite resulted in enhanced electrochemical performances compared to bare electrodes and graphene-modified electrodes. As hydrogen peroxide (H2O2) is one of the most common by-products of biological metabolic reactions, a non-enzymatic hydrogen peroxide (H2O2) sensor platform was developed to investigate the potential of G/TiO2 nanocomposite in biosensing applications. The resulting H2O2 sensor exhibited high sensitivity with a limit of detection (LOD) of 56.89 nM. Subsequently, a versatile biosensor platform was constructed using 1-pyrenebutyric acid N-hydroxysuccinimide ester (PSE) as the biolinker. The performances of both graphene and G/TiO2 based immunosensing platforms were evaluated for the detection of Dengue virus antibodies (DENV IgG). For the first time, a consensus envelope glycoprotein domain III (cEDIII) of dengue virus was employed as the biorecognition element for improved selectivity towards DENV IgG, even when challenged against the structurally similar Zika virus antibodies (ZIKV IgG). Moreover, the cEDIII protein was obtained via a novel plant-based molecular pharming approach which offers remarkable scalability and safety. Both graphene and G/TiO2 platforms showed promising results in dengue sensing with good sensitivity and selectivity. In addition, the feasibility of the immunosensing platforms in real sample was investigated through the detection of dengue antibodies in mouse serum samples, where both platforms successfully discriminated positive samples from the negative control, suggesting the potential of the immunosensor platforms in replacing conventional diagnostic methods. The G/TiO2-based immunosensor displayed superior sensing performance compared to the graphene-based platform, with wider linear working range (62.5 pg/mL to 2 ng/mL) and lower limit of detection (LOD) of 2.81 pg/mL. Finally, the biocompatibility enhancement effect provided by the incorporation of TiO2 nanoparticles onto graphene was studied via cytotoxicity assessments and comparison study on both graphene and G/TiO2 nanocomposites. Results showed that the cytotoxicity of the nanomaterials is exposure time and dose-dependent, in which higher concentrations and prolonged incubation periods lead to higher magnitude of losses in cell viability. In general, G/TiO2 nanocomposites exhibited lesser cytotoxic effects on both cell lines compared to graphene with a half maximal inhibitory concentration (IC50) of greater than 500 µg/ml and around 25 µg/ml for MRC5 cells and HaCaT cells, respectively, at 24-hour time-point. The satisfactory biocompatibility of G/TiO2 nanocomposites indicated its potential in various delicate biomedical applications such as in-vivo biosensing where the attribute is highly required.